Pemberdayaan Usaha Garam Rakyat Dalam Meningkatkan Kualitas Garam Menggunakan Teknik Geomembran LDPE di Kelurahan Talise Kota Palu - Nelky Suriawanto; Nurhayati; Wendy Muhammad Fadhli; M. Syahril; Nivita Nanda Gabrela (Yayasan Literasi Sains Indonesia, 2022)
Salt is an important commodity that is widely used from consumption to industry. Talise Village is the only salt-producing village in Palu City because the area is mostly located on the coast of Palu Bay. LDPE (Low Density Polyethylene) geomembrane technology is an empowerment program focused on increasing the production and quality of salt products and improving welfare by increasing the income of salt farmers. The purpose of this activity is to apply LDPE geomembrane technology to salt farmer groups in Talise in producing and improving the quality of SNI-standard salt as consumption salt and increasing awareness of salt farmers to use technology in managing their salt ponds. The method used is the stages of socialization, pre-production and production. The results of this activity program, namely the use of LDPE geomembrane technology on crystal tables, have increased the quantity and quality of salt for salt farmers in Talise Village, Mantikulore District, Palu City, Central Sulawesi. In addition, crop yields have increased threefold and harvest time is 3 to 4 days faster than conventional methods.